Transformasi Pendidikan Islam: Moderasi Beragama Dalam Tradisi Pesantren Salaf Di Era Global - Ach. Sayyi; Rofiqi (Universitas Islam Lamongan, 2024)
Globalization poses significant challenges for salaf pesantren, especially in maintaining classical scholarly traditions amidst the demands of modernity. On the other hand, the rise of intolerance and radicalism reinforces the urgency of integrating values of religious moderation in pesantren education. This research aims to develop a model for integrating religious moderation within the salaf pesantren tradition to enhance its relevance in the era of globalization. The research method used is a qualitative approach based on literature studies by analyzing literature related to religious moderation, salaf pesantren, and the transformation of Islamic education. Data is analyzed through critical synthesis stages to formulate a model for implementing religious moderation. The research results indicate that the integration of values of religious moderation such as tolerance, national commitment, anti-violence, and appreciation of local culture can be applied through interdisciplinary approaches, practice-based learning, educator training, and collaboration with external parties. The process of developing this model includes identifying core values, adjusting the curriculum based on yellow books, using contextual learning methods, and conducting systematic evaluation and continuous monitoring. This model enables salaf pesantren not only to maintain their traditional identity but also to act as agents of change that create adaptive and inclusively-minded Muslim generations.